Rapid outer-surface protein C DNA tattoo vaccination protects against Borrelia afzelii infection - Wagemakers, A; Mason, L M K; Oei, A; de Wever, B; van der Poll, T; Bins, A D; Hovius, J W R (Gene therapy, 2014)
Borrelia afzelii is the predominant Borrelia species causing Lyme borreliosis in Europe. Currently there is no human vaccine against Lyme borreliosis, and most research focuses on recombinant protein vaccines against Borrelia burgdorferi sensu stricto. DNA tattooing is a novel vaccination method that can be applied in a rapid vaccination schedule. We vaccinated C3H/HeN mice with B. afzelii strain PKo OspC (outer-surface protein C) using a codon-optimized DNA vaccine tattoo and compared this with recombinant protein vaccination in a 0–2–4 week vaccination schedule. We also assessed protection by DNA tattoo in a 0–3–6 day schedule. DNA tattoo and recombinant OspC vaccination induced comparable total IgG responses, with a lower IgG1/IgG2a ratio after DNA tattoo. Two weeks after syringe-challenge with 5 × 10 5 B. afzelii spirochetes most vaccinated mice had negative B. afzelii tissue DNA loads and all were culture negative. Furthermore, DNA tattoo vaccination in a 0–3–6 day regimen also resulted in negative Borrelia loads and cultures after challenge. To conclude, DNA vaccination by tattoo was fully protective against B. afzelii challenge in mice in a rapid vaccination protocol, and induces a favorable humoral immunity compared to recombinant protein vaccination. Rapid DNA tattoo is a promising vaccination strategy against spirochetes.